2016
DOI: 10.14814/phy2.13032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise-induced muscle damage on vascular function and skeletal muscle microvascular deoxygenation

Abstract: This paper investigated the effects of unaccustomed eccentric exercise‐induced muscle damage (EIMD) on macro‐ and microvascular function. We tested the hypotheses that resting local and systemic endothelial‐dependent flow‐mediated dilation (FMD) and microvascular reactivity would decrease, V˙normalO2max would be altered, and that during ramp exercise, peripheral O2 extraction, evaluated via near‐infrared‐derived spectroscopy (NIRS) derived deoxygenated hemoglobin + myoglobin ([HHb]), would be distorted followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 74 publications
4
22
1
8
Order By: Relevance
“…Baseline and post-cuff release time-averaged mean velocity (cm/s) values per 3 s were calculated with the manufacturer's on-screen software and time aligned with diameter to calculate shear rate [shear rate (s Ϫ1 ) ϭ 4 ϫ mean blood velocity (cm/s)/diameter (cm)]. After cuff deflation, the stimulus for arterial dilation was calculated as the area under the shear rate curve (AUCSR) with the trapezoid rule (7,32). The postocclusive reactive hyperemic response was assessed as the peak blood flow response following cuff release (15).…”
Section: Methodsmentioning
confidence: 99%
“…Baseline and post-cuff release time-averaged mean velocity (cm/s) values per 3 s were calculated with the manufacturer's on-screen software and time aligned with diameter to calculate shear rate [shear rate (s Ϫ1 ) ϭ 4 ϫ mean blood velocity (cm/s)/diameter (cm)]. After cuff deflation, the stimulus for arterial dilation was calculated as the area under the shear rate curve (AUCSR) with the trapezoid rule (7,32). The postocclusive reactive hyperemic response was assessed as the peak blood flow response following cuff release (15).…”
Section: Methodsmentioning
confidence: 99%
“…What has an influence on O2 delivery and O2 utilization, which are factors having an influence on phase II τ, in a DOMS condition? At least local superficial femoral arterial function in the muscles forced to perform ECC was observed to be impaired 74) , though systemic circulatory response, e.g., HR 11,14,71,73) and arterial vascular function in nonlocal regions that are not affected by ECC 74) , is not likely to change after ECC. A few studies have suggested The subjects (n = 8) performed a series of 5-min square-wave transitions from rest to 60 or 90-W cycling exercises using a bicycle ergometer.…”
Section: Impact Of Exaggerated Initial Ventilatory Response On Musclementioning
confidence: 95%
“…We are particularly interested in understanding the influence of local muscular activity in the microcirculatory adaptation to movement, a critical aspect of restoration of walking and a high priority for rehabilitation in some forms of stroke. The balance of microvascular dynamics is critical to understand the impact of muscle activity on the lower limb perfusion, and several studies have suggested that concentric plantar flexion changes local blood flow [3] . However, changes related with dorsiflexion activity have not been previously addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, changes related with dorsiflexion activity have not been previously addressed. Many of our daily life activities take place in the stuprightanding position and involve walking [3][4] . At the lower limbs extremities, calf muscles play a fundamental role in local vascular structures due to the external pressure exerted on the vessel walls, and that includes microcirculation [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation